GENDER ASPECTS OF DAYRA PERFORMANCE IN THE MASTER-APPRENTICE TRADITION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the gender aspects of dayra (frame drum) performance in the context of traditional Uzbek music art. It specifically analyzes the unique role and achievements of female dayra players in modern musical performance. The study highlights the interrelation between the master-apprentice tradition and gender dynamics, providing a gender-based analysis of renowned dayra performers and their schools in Uzbekistan. Furthermore, it discusses the issues of gender equality and innovative approaches based on scholarly and methodological sources. The article also addresses gender challenges in dayra performance art, the position of female performers, and the interplay between traditional and contemporary styles.